2021
DOI: 10.3390/e23111400
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous and Radiating Composite Fluids

Abstract: We consider the energy conditions for a dissipative matter distribution. The conditions can be expressed as a system of equations for the matter variables. The energy conditions are then generalised for a composite matter distribution; a combination of viscous barotropic fluid, null dust and a null string fluid is also found in a spherically symmetric spacetime. This new system of equations comprises the energy conditions that are satisfied by a Type I fluid. The energy conditions for a Type II fluid are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Even though the general solution is difficult to obtain, a physically realistic fluid distribution should follow the null, weak, strong and dominant energy conditions [46]- [48] simultaneously within the stellar boundary. Here, we have studied the energy conditions [49,50] for the present stellar configuration and found that they are well satisfied.…”
Section: Energy Conditionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Even though the general solution is difficult to obtain, a physically realistic fluid distribution should follow the null, weak, strong and dominant energy conditions [46]- [48] simultaneously within the stellar boundary. Here, we have studied the energy conditions [49,50] for the present stellar configuration and found that they are well satisfied.…”
Section: Energy Conditionsmentioning
confidence: 79%
“…In the case of a physically viable model of a compact star, the necessary energy conditions [49], [50] must be fulfilled at all internal points as well as at the surface of compact stars. For the present model, we have checked the energy conditions within the parameter space used here and found that they are in good agreement with the prescribed conditions.…”
Section: Energy Conditionsmentioning
confidence: 99%
“…The energy conditions for the Type II fluid (as shown in [21,67,69]) are -The null energy condition:…”
Section: The Generalised Radiating Boulware-deser Solutionmentioning
confidence: 99%
“…For a charged anisotropic compact object the energy conditions namely (i) null energy condition (NEC), (ii) weak energy condition (WEC), (iii) dominant energy condition (DEC) and (iv) strong energy condition (SEC) should be satisfied [99,100]. We have determined the mathematical expressions for different energy conditions using the approach discussed in [99] and are given below ρ + pr ≥ 0, The NEC, WEC, DEC and SEC are plotted in Figs. 10, 11, 12, 13, 14 and 15 respectively.…”
Section: Energy Conditionsmentioning
confidence: 99%